The cashflow quadrant : rich Dad's guide to financial freedom - Kiyosaki, Robert T., 1947- (Paradise Valley, Ariz. : TechPress, 1998)
The cashflow quadrant. Bringing out the best in you. How to be a successful "B" and "I".
Keywords: Finance; Economics; Business; Investments; Success in business; Investments; Finance, Personal